The Tools & tecniques of income tax planning / Stephan Leimberg,...[et al.] - Jackson, Michael S.
This single-volume reference takes you through all the income tax topics your clients may encounter, no matter where they originate, providing easy-to-understand, practical guidance for situations that are often confusing.